Bridging the climate science-policy gap through exchange platforms in West Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
This project organizes platforms for scientists and policymakers to exchange climate information and create better policies to build climate-smart food systems in West Africa.